THE PROVISION OF CLAMSHELL FLOUR IN THE RATION OF CARCASS AND PHYSICAL COMPOSITION OF ISA BROWN CHICKEN AFTER REJECT - I P. R., Andikayana; Dewi, G. A. M. K.; Putra, I G. A. A. (Jurnal Peternakan Tropika; Vol 8 No 3 (2020): Vol. 8 No. 3 Tahun 2020; September - December, 2020)
This study aims to determine the effect of commercial ration supplemented with clamshell flour for carcass and the physical composition carcasses of Isa Brown chicken after reject. This research was carried out in Pasedahan Village, Manggis District, Karangasem Regency for four weeks. The design used in this study was a completely randomized design (CRD) with four treatments, each treatment using five replications and each unit using three Isa Brown chickens. The treatments given were commercial rations without adding clamshell flour (A / control), commercial rations added 1%, 2% and 3% clamshell flour (B, C and D). The variables observed in this study included cutting weight, carcass weight, meat percentage, bone percentage, skin and fat. The results of this study showed that the addition of 1%, 2%, and 3% clamshell flour in commercial rations showed higher results on the percentage of bones, fat and skin significantly (P <0.05) compared to chickens that received treatment A (control) . While the addition of 1%, 2%, and 3% clamshell flour in commercial rations on cutting weight, carcass weight, and percentage meat of higher were not significantly different (P> 0.05) compared to chickens that received treatment A (control). Based on the results of this study it can be concluded that the addition of 1%, 2% and 3% clamshell flour in commercial rations did not affect the cutting weight, carcass weight, percentage of meat produced but an increase in the percentage of bone, skin and fat. Keywords : Isa Brown Chicken, clamshell flour, carcass, carcass physical composition.